Conceptual framework: The mediating effect of self-efficacy in the relationships of self-leadership, knowledge sharing, and innovative work behaviour - Ibus, Salbeha; Ismail, Fadillah (Human Resource Management Academic Research Society, 2018)
There are substantial empirical evidences on the influence of self-efficacy towards organisational performance. However, the mediating effect of self-efficacy in the relationships of self-leadership and knowledge sharing with innovative work behaviour, particularly in the educational context, remains inadequately explored. Addressing that, this study attempts to contribute in-depth insights on the factors that influence innovative work behaviour in the higher education institutions based on a proposed conceptual framework to promote innovative work behaviour among Malaysian academics.